2002
DOI: 10.1002/jctb.649
|View full text |Cite
|
Sign up to set email alerts
|

Operating and scale‐up factors for the electrolytic removal of algae from eutrophied lakewater

Abstract: Electrolytic removal of algae was conducted in batch and continuous reactors to investigate operating factors affecting removal ef®ciency and to explore engineering relationships which could be useful for operation and scale-up. The system integrated both electro-¯occulation and electrootation mechanisms by using polyvalent metal anodes and inert metal cathodes. Batch reactor studies con®rmed that high electrical input power or higher electrical current achieved higher and faster removal ef®ciencies. Natural l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
38
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 88 publications
(39 citation statements)
references
References 3 publications
1
38
0
Order By: Relevance
“…Poelman et al found that excellent separation of cyanobacteria (>90%) could be achieved by electrolytic flocculation, with relatively low energy consumption (0.3 kWh/m 3 ) [24]. Alfafara et al demonstrated that the electroflotation alone also exhibited a maximum algae removal of 40-50% [25]. While complete removal of algae was obtained by Ghernaout et al when treating Keddara raw water by the electrocoagulation using aluminum electrodes [26].…”
Section: Introductionmentioning
confidence: 96%
“…Poelman et al found that excellent separation of cyanobacteria (>90%) could be achieved by electrolytic flocculation, with relatively low energy consumption (0.3 kWh/m 3 ) [24]. Alfafara et al demonstrated that the electroflotation alone also exhibited a maximum algae removal of 40-50% [25]. While complete removal of algae was obtained by Ghernaout et al when treating Keddara raw water by the electrocoagulation using aluminum electrodes [26].…”
Section: Introductionmentioning
confidence: 96%
“…In the case of 10 V, after 60 min the efficiency was reversed to better results, which is according with the results showed in this research, Xu et al (2010), who obtained greater efficiency in the first minutes of the sedimentation process. The applied current is also an important variable in the EF process (Vandamme et al, 2011), as a result, higher electrical power produced more flocculants to enhance algal flocculation (Alfafara et al, 2002). All these results, as well as those obtained during the sedimentation time are summarized in Table 1.…”
Section: Effect Of Voltagementioning
confidence: 92%
“…Although the algae studied were different, it can be considered that the results were similar to those obtained in this investigation. Research conducted by Alfafara et al (2002) who studied the Microcystis sp., concluded that electro-flotation alone is not efficient but the combination of electro-flocculation and electro-flotation causes >90% removal of it. Many researchers have developed techniques for growing and harvesting algae for further use as biodiesel, many of them are summarized in the review conducted by Chen et al (2011) where an analysis of the latest research is made up to 2011.…”
Section: Comparison Between Ef and Other Algae Harvesting Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…This process has been run in both batch and continuous mode and found that higher power positively correlated with increased algal cell separation in eutrophic lake water (Alafara et al 2002). The advantage of this method is there is no need for the addition of chemicals to induce separation.…”
Section: Electrolytic Flotationmentioning
confidence: 98%